The influence of intercultural communication on the decision of Middle Eastern students to study in Malaysia / Yassin Madani Abdul Alkadir - Abdul Alkadir, Yassin Madani (Institute of Graduate Studies, UiTM, 2017)
Consideration of the influence of intercultural communication factors on the decision of students to study overseas is a new tool that integrates the field of communication and decision making sciences, and is widely used in educational institutions in highly diversified educational environments. This study aimed to identify the most important and critical intercultural and non-intercultural communication factors that influence Middle Eastern students to study in Malaysia. The study was conducted in three stages to address the objectives of the study. The first stage involved group discussions and interviews with a selected group of Middle Eastern students from the undergraduate to postgraduate levels. The research literature was reviewed to ascertain some factors affecting students’ decisions to study overseas, and this stage led to the identification of some preliminary factors that have encouraged Middle Eastern students to study in Malaysia. This stage provided a clear picture and understanding of intercultural and non-intercultural communication factors that have had an impact on the decision of Middle Eastern students to study in Malaysia. It also provided some insights on the intercultural communication barriers Middle Eastern students encountered in Malaysia and which may have serious impacts on the flow of Middle Eastern students in the future…